KINERJA TIM PENILAI ANGKA KREDIT JABATAN FUNSIONAL DOKTER DI RUMAH SAKIT UMUM DAERAH UNDATA PALU PROVINSI SULAWESI TENGAH - Huraerah, Rosita (Katalogis, 2016)
Implementation of this research aims to identify and analyze the performance of Credit Score Assessment Team Functional Doctors Hospital Regional General Undata Palu, Central Sulawesi province. This research uses descriptive qualitative approach. The location of this research at the General Hospital Undata Palu of Central Sulawesi. Informants in this study is the party who is deemed to know in depth the various matters related research problems, so as to provide the necessary information and data as well as accurate. Therefore, researchers determine the informant is as much as five (5) members, namely those who are included in the assessment team credit points, doctor who had been working the number of credits, as well as employees of the General Hospital of Undata Palu in charge of personnel affairs. Determination of informants in this study was done by using purposive. Data collected through observation techniques, interviews, and documentation. Data analysis techniques including data collection, data reduction, data presentation, and conclusion/verification. Based on the results of research and discussion Performance Assessment Team concluded that Credit Score Functional Doctors Hospital Regional General Undata Palu, Central Sulawesi province viewed from the theory put forward by Lenvine performance, overall not optimal. This is because the responsiveness indicators and indicators Responsibilita not running optimally. While the views of the indicators have been realized with optimal Accountability.